PENGARUH ASPEK FASILITAS PENUNJANG TOWER TERHADAP PELAYANAN PENERBANGAN PERUM LPPNPI UNIT MUARA BUNGO - Rafi Mikail Akbar; Abdul Mu’ti Sazali; Syahrul Aman (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
With adequate facilities for the AFIS unit, the safety and comfort aspects will be guaranteed in aviation safety services. However, the reality is different from what happens on the ground. The purpose of this research is to create a comfortable environment and provide equipment that is in accordance with the ACO contained in the CASR Part 170 sub part 170.G (170.060) document regarding the operational requirements of air traffic service. However, in the implementation of providing flight communication services, the tower which should be a personnel workspace is not used properly. As a result, several difficulties arise that interfere with the performance of personnel such as noise disturbances and external parties. The research method used is descriptive qualitative method. The use of this method is to analyze, describe and summarize various conditions, situations from various data collected in the form of interviews or observations. Data collection techniques carried out in the form of interviews in the form of questions and answers by resource persons who act as informants to obtain data. Then observation, because observation has specific characteristics compared to other techniques. And finally, through library studies, by reviewing books, literature, and various reports related to the problem to be solved. The results of this study indicate that the performance of ACO personnel in providing services can disrupt the process of giving and receiving information to pilots.